The William Hoy story : how a deaf baseball player changed the game - Churnin, Nancy; Tuya, Jez (Chicago, Illinois : Albert Whitman and Company, 2016)
All William Ellsworth Hoy wanted to do was play baseball. After losing out on a spot on the local deaf team, William practiced even harder—eventually earning a position on a professional team. But his struggle was far from over. In addition to the prejudice Hoy faced, he could not hear the umpires’ calls. One day he asked the umpire to use hand signals: strike, ball, out. That day he not only got on base but also changed the way the game was played forever. William “Dummy” Hoy became one of the greatest and most beloved players of his time!
Keywords: Hoy, William, -- 1862-1961 -- Juvenile literature; Baseball players -- United States -- Biography -- Juvenile literature; Deaf athletes -- United States -- Biography -- Juvenile literature; Hoy, William, -- 1862-1961.; Deaf athletes -- United States -- Biography; Biographies